PENGEMBANGAN MEDIA MONOPOLI JEJAK PETUALANG BERMUATAN KEARIFAN LOKAL KOTA SEMARANG GUNA PENINGKATAN KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Sa'diyah, Chalimatus; Eko Handoyo; Wasino (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Numeracy skills are competencies that play an important role in supporting the quality of a nation. This skill is the focus of learning in the field of education, especially at the basic education level. The background of this study is based on the results of observations and interviews with fifth grade teachers of SD Islam Cahaya Ilmu showing that students' numeracy skills still need to be improved. Students look less active in participating in learning related to counting, less focused, bored and bored and even sleepy so that students still have difficulty in understanding story problems related to calculation. This research aims to develop media as well as test the validity, feasibility and effectiveness of monopoly media of adventurous traces with local wisdom of Semarang city. This research is a type of RnD research with the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research sample used was class VA as the experimental class and class VB as the control class with a total of 24 students. The data collection technique uses qualitative data obtained through observation, interviews, questionnaires / surveys and quantitative data obtained through validity and effectiveness tests from the validation results of media experts, material experts and linguists as well as teacher and student responses related to the use of media. The results showed that the results of testing the prerequisites of research analysis using the normality test with the aim of knowing the distribution of normally distributed data or not. This test uses the shapiro wilk test because the data used is less than 50 with the help of Ms. Excel and SPSS 29. Based on the results of the normality test, the data obtained from the experimental class pretest results of 0.88 and posttest of 0.092, this shows that the data is normally distributed because the results obtained are more than the significance level of 0.05. Homogeneity test using SPSS is using Levene with the results of 0.758 (pretest) and 0.635 (Posttest) which means more than 0.05, meaning that the data from the pretest and posttest results are homogeneous. The results of the media expert validity test obtained a score of 4.7 in the very feasible category, material experts showed a score of 4.19 including the feasible category and linguists 4 classified as feasible. The results of the experts' validation show that this media is feasible, practically effective and significant to improve students' numeracy skills. Keywords: Media Development, Adventurer's Trail Monopoly, Numeracy